Association of Rising Violent Crime With Blood Pressure and Cardiovascular Risk: Longitudinal Evidence From Chicago, 2014–2016. (15th August 2019) - Tung, Elizabeth L; Chua, Rhys F M; Besser, Stephanie A; Lindau, Stacy Tessler; Kolak, Marynia; Anyanwu, Emeka C; Liao, James K; Tabit, Corey E
Abstract: BACKGROUND: The purpose of this study was to examine the longitudinal association between rising violent crime and elevated blood pressure (BP). METHODS: We analyzed 217, 816 BP measurements from 17, 783 adults during a temporal surge in violent crime in Chicago (2014–2016). Serial observations were abstracted from the electronic health record at an academic medical center and paired to the City of Chicago Police Data Portal. The violent crime rate (VCR) was calculated as the number of violent crimes per 1, 000 population per year for each census tract. Longitudinal multilevel regression models were implemented to assess elevated BP (systolic BP ≥ 140 mm Hg or diastolic BP ≥ 90 mm Hg) as a function of the VCR, adjusting for patient characteristics, neighborhood characteristics, and time effects. Secondary dependent measures included elevated heart rate, obesity, missed outpatient appointments, all-cause hospital admissions, and cardiovascular hospital admissions. RESULTS: At baseline, the median VCR was 41.3 (interquartile range: 15.2–66.8), with a maximum rise in VCR of 59.1 over the 3-year surge period. A 20-unit rise in the VCR was associated with 3% higher adjusted odds of having elevated BP (95% confidence interval [CI]: 1.01–1.06), 8% higher adjusted odds of missing an outpatient appointment (95% CI: 1.03–1.13), and 6% higher adjusted odds of having a cardiovascular-related hospital admission (95% CI: 1.01–1.12); associations were not significant for elevated heart rate and obesity. CONCLUSION: Rising violent crime was associated with increased BP during a temporal crime surge.